2010
DOI: 10.1021/jp911993f
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Flexibility of C8-Phenoxyl-2′-deoxyguanosine Nucleotide Adducts

Abstract: Previous computational work suggests that isolated C8-phenoxyl-2'-deoxyguanosine nucleoside adducts preferentially adopt a syn orientation about the glycosidic bond, which is the first step in the mechanism by which many bulky C8 adducts exert their mutagenic effects. Since it is not clear whether these results can be directly extrapolated to the preferred conformation in DNA helices, approaches that more accurately reflect the physiological environment were used in the present study to understand the anti/syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
91
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(102 citation statements)
references
References 87 publications
9
91
2
Order By: Relevance
“…In this model, the phosphate oxygen bonded to the 5′-neighboring nucleotide in DNA was capped with a hydrogen atom and the Na + ion was placed between the two non-capped phosphate oxygens. The structures were energy minimized in water using PCM-B3LYP-D3/6–31G(d), since our previous study has shown that the structural properties of modified nucleotides are best characterized in solvent (water) with a sodium ion to counter the phosphate charge ( 55 ). Single-point energy calculations were carried out using B3LYP-D3/6–311+G(2df,p) for the nucleobase and nucleoside minima and PCM-B3LYP-D3/6–311+G(2df,p) for the nucleotide minima.…”
Section: Methodsmentioning
confidence: 99%
“…In this model, the phosphate oxygen bonded to the 5′-neighboring nucleotide in DNA was capped with a hydrogen atom and the Na + ion was placed between the two non-capped phosphate oxygens. The structures were energy minimized in water using PCM-B3LYP-D3/6–31G(d), since our previous study has shown that the structural properties of modified nucleotides are best characterized in solvent (water) with a sodium ion to counter the phosphate charge ( 55 ). Single-point energy calculations were carried out using B3LYP-D3/6–311+G(2df,p) for the nucleobase and nucleoside minima and PCM-B3LYP-D3/6–311+G(2df,p) for the nucleotide minima.…”
Section: Methodsmentioning
confidence: 99%
“… 64 Calculations (B3LYP/6-31G(d)) reveal that anti -structures are less stable than syn -structures, mainly since all syn minima contain an O5′–H···N3 hydrogen bond (1.80–1.96 Å). 55 , 65 67 The predicted syn -preference for the C-linked 8arylG nucleosides is supported by NMR spectra that exhibit a downfield shift of H2′, C1′, C3′ and C4′ and an upfield shift of C2′ compared to the corresponding signals for native G. 67 , 68 Solid-state structures of C-linked 8arylG nucleosides, including an 8-quinolyl derivative (QG) 24 and an ( N , N -dimethylaniline)guanosine analog, 69 are also syn . As a specific example, DFT calculations predict the syn orientation of the smallest (unsubstituted) 8-phenylG (PhG) derivative ( Fig.…”
Section: Nucleoside Synthesis Structure and Propertiesmentioning
confidence: 99%
“…It has also been shown previously that many 8-substituted purines show a preference for the syn conformation (55,56). However, calculations suggested a syn / anti equilibrium to be present in DNA helices for other analogues (57). The preferred orientation of the modified base around the glycosidic bond in duplex DNA depends on the hydrogen bonding preferences, which can change depending on the bulky substituent and can improve the relative stability of Hoogsteen pairs.…”
Section: Discussionmentioning
confidence: 99%